2015
DOI: 10.1248/bpb.b14-00583
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic Compounds from <i>Liriodendron tulipifera</i> Attenuating HSC-T6 Proliferation and TNF-α Production in RAW264.7 Cells

Abstract: The inhibition of hepatic stellate cell (HSC) proliferation has been considered as an effective therapeutic target for the treatment of liver fibrosis. The methanolic extract of Liriodendron tulipifera showed significant inhibitory activity against the proliferation of HSCs. Bioactivity-guided isolation afforded twelve compounds including ( )-sesamin (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The second target involves antagonising the inflammatory cytokines released from hepatic macrophages, such as IL-1 and TNF-α, 41 or promoting the apoptosis of activated HSCs, thereby attenuating hepatic fibrosis. 42 43 …”
Section: Introductionmentioning
confidence: 99%
“…The second target involves antagonising the inflammatory cytokines released from hepatic macrophages, such as IL-1 and TNF-α, 41 or promoting the apoptosis of activated HSCs, thereby attenuating hepatic fibrosis. 42 43 …”
Section: Introductionmentioning
confidence: 99%
“…Supernatant cultures of Lactobacillus kefiri BCRC14011, Lactobacillus kefiranofaciens BCRC16059, L. kefiranofaciens M1, L. kefiri M2, Leuconostoc mesenteroides M3, and Lactococcus lactis M4 can increase macrophage expression of IL-12, IL-6, IL-1β, and TNF-α in macrophages in vitro, and have strong *refers to the comparison between cells in the cell control group not exposed to any treatment and other groups exposed to different concentrations of SQ0048 without inhibitor treatment; it also refers to the comparison between groups without inhibitors and corresponding groups with inhibitors at the same concentration of SQ0048; # refers to the comparison between cells in the inhibitor control group with inhibitors but not SQ0048 and other groups with inhibitors. antibacterial activity (31). L. crispatus and L. iners can increase expression of IL-6, IL-8, and TNF-α (32).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of liver fibrosis is very complex. Liver damage caused by virus, drug and other factor can stimulate macrophages to release inflammatory cytokines, these cytokines can participate in the production and degradation of extracellular collagen, and the activation and apoptosis of hepatic stellate cell through a variety of ways ( 22 ), which eventually leads to fibrosis. It has been found that H 2 S can promote apoptosis of vascular smooth muscle cells by downregulating the level of apoptosis inhibitors such as Bcl-2 and NF-κB ( 23 ).…”
Section: Discussionmentioning
confidence: 99%